Applying GNSS and DTM technologies to monitor the ice balance of the Horcones inferior glacier, Aconcagua region, Argentina - Lenzano, María Gabriela (2013)
This work provides results and analysis of the behavior in a reconstituted debris covered glacier, Horcones Inferior (HIG). This glacier is located at 32° 41′ S and 69° 57′ W in the Aconcagua region, Mendoza, Argentina. The HIG has experienced surges events in 1984 and 2003. GNSS techniques and Digital Terrain Models (DTMs) derived from ASTER optical imagery, were used to detect movements and altimetric changes of the HIG in the 2001-2012 period. Based on a GNSS semi - continuous station, N and E mean velocities of 0.9 cm/d and 1.1 cm/d and in U direction were 1.1 cm/d and 1.5 cm/d were obtained respectively in 2009?2010 period. Additionally, GNSS profiles showed a velocity range between 0.5 cm/d and 2.8 cm/d. Finally, through a DTM comparison the altimetric change before and after the last surge in 2003 was obtained. The applied techniques allowed accurate and reliable change detection of the HIG.